Relationship between Mild Genu Varum and Genu Valgum with Degenerative Hip and Knee Disease: A Cadaveric Study - Raymond W. Liu; Douglas S. Weinberg; Jonathan J. Streit; Colin E. Lasko; Daniel R. Cooperman (Journal of Limb Lengthening & Reconstruction)
Background: Varus and valgus deformity of the knee are relatively common conditions, and clinical studies have associated both with increased knee arthritis in high-risk patients. However, the consequences of these deformities in a randomly collected cadaveric population remain unclear. Hypothesis: We investigated whether varus and valgus deformity are associated with hip and knee arthritis in an osteological collection. Materials and Methods: We studied 430 well-preserved cadaveric skeletons ranging from 40 to 79 years of age at death. Specimens with obvious traumatic, infectious, rheumatologic, or endocrine abnormalities were excluded. Photographs of the femur and tibia in the standard anatomic position were measured for mechanical lateral distal femoral angle (mLDFA) and medial proximal tibial angle (MPTA), and analysis was based on deviation from the mean for each parameter. Degenerative disease of the hip and each compartment of the knee were graded, and associations were assessed with multiple regression analysis. Results: Mean age was 56 ± 10 years, mean mLDFA was 88.1° ± 2.2°, and mean MPTA was 87.2° ± 2.4°. Multiple regression analysis demonstrated strong correlations between age and degenerative disease of the hip and knee (P < 0.0005 for both). Degenerative disease of the hip was not related to knee alignment. Degenerative disease of the knee was increased by combined varus deformity but was not affected by valgus deformity. Conclusions: Mild varus deformity of the knee was significantly related to degenerative disease of the knee but not the hip in our study. In contrast, mild valgus deformity was not related to degenerative disease of the hip or the knee. These data are likely most relevant to asymptomatic patients with genu varum and valgum. Level of Evidence: N/A, anatomic study.